Formal and informal equity funding in Chile - José Ernesto Amorós; Miguel Atienza; Gianni Romani (Estudios de Economía, 2008)
This paper explores the state of formal and informal equity sources currently available for financing entrepreneurial activity in Chile. By integrating theoretical perspectives regarding formal and informal equity funding and information gathered from the Global Entrepreneurship Monitor (GEM) surveys, the paper argues that despite the favorable environment existing in Chile for equity investment, these markets are still incipient and strongly dependent on public policies. In this respect it is proposed that public intervention to address equity gaps in Chile should also adopt a demand-side perspective, aimed at improving the quality of investment opportunities, and should incorporate a geographical dimension, considering the particularities and financial needs of non-metropolitan regions.
Keywords: G24; M13; 330; entrepreneurship; venture capital; business angels; informal investment; equity gaps